Internal initiation of translation on the vesicular stomatitis virus phosphoprotein mRNA yields a second protein. - Herman, R C (1986)
In vitro translation of a mixture of the vesicular stomatitis virus (VSV) polyadenylated mRNAs yielded a previously undetected protein with a molecular weight of approximately 7,000 (7K protein). Hybrid-arrested translation demonstrated that both the 7K protein and the VSV phosphoprotein (P protein) were encoded by the P protein message. Immunoprecipitation of the 7K protein with monoclonal antiserum directed against the P protein indicated that the two products were encoded in the same open reading frame. A protein of approximately the same size was immunoprecipitated from cytoplasmic extracts of VSV-infected cells by both the polyclonal and monoclonal antisera, and it is likely that it was a previously unrecognized viral gene product. Translational mapping of the P protein mRNA in vitro indicated that the 7K protein was encoded in the 3' one-third of the sequence. The synthesis of the 7K protein in vitro was unaffected by hybrid arrest conditions which blocked the 5' two-thirds of the mRNA and inhibited synthesis of the P protein. These results imply that the ribosomes bind and initiate translation internally on the P protein mRNA at a site located hundreds of nucleotides downstream from the capped 5' end.